Problematika Aplikasi Sistem Informasi Manajemen Nikah Dalam Praktik Pernikahan Pada Masyarakat Muslim Di Kelurahan Blimbing - Novitasari, Novitasari; Santosa, Imam; Lestari, Soetji (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Currently registration can be done online through the Marriage Management Information System (SIMKAH) application. This study aims to identify problems of the application of marriage management information systems in marriage practices in the muslim community in Blimbing Village. This study uses a descriptive qualitative research method. Data collection techniques through observation, in-depth interviews, and documentatiton. Data analysis tchniques through data collection, data condensation, data presentation, and conclusions. The results of the study indicate that the condition of the Blimbing Village community is that there are categories of understanding a little, understanding, and very understanding of the SIMKAH application. The application of the SIMKAH application in marriage practices is used by the Muslim community, namely prospective brides and grooms, married brides and grooms, families of prospective brides and grooms, and the head of the KUA Paciran District. The problems with the SIMKAH application are that some muslims do not understand the SIMKAH application, the problem of data unsynchronization, widows under 19 years old are asked for a dispen permit from the religious court and there is no delete menu when the marriage certificate has been printed or after the examination is complete which is canceled. The role of the government in dealing with these problems is to provide socialization, guidance, assistance, and periodic evaluation. The conclusion is that the problematic application of SIMKAH in marriage practices in the muslim community in Blimbing Village needs to be resolved with assistance from the government so that marriage practices can run well and smoothly.